2021
DOI: 10.1155/2021/9973743
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Albumin to D-Dimer Ratio in Advanced Gastric Cancer

Abstract: Gastric cancer (GC) is one of the most common malignancies worldwide. Notably, patients with advanced GC have a poor prognosis and quality of life, prompting the need for further studies on its prognostic markers. Among these, albumin and D-dimer are often used as prognostic factors in the prediction of a variety of tumors. Moreover, the albumin to D-dimer ratio (ADR) may be an improved predictor of chemotherapy effect and survival compared to albumin and D-dimer alone, but few studies have investigated this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 58 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…In the present study, we used the DAR, which reflects the hypercoagulative status and malnutrition. DAR has been used as an independent prognostic marker in infections, malignancies, and other diseases [ 6 , 7 ], Therefore, it is not surprising that the multivariate analysis in this study revealed that DAR independently predicted poor aSAH outcomes better than D-dimer alone.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present study, we used the DAR, which reflects the hypercoagulative status and malnutrition. DAR has been used as an independent prognostic marker in infections, malignancies, and other diseases [ 6 , 7 ], Therefore, it is not surprising that the multivariate analysis in this study revealed that DAR independently predicted poor aSAH outcomes better than D-dimer alone.…”
Section: Discussionmentioning
confidence: 64%
“…Several blood tests might help predict outcomes [ 3 ], including tests for D-dimer, where high levels indicated poor outcomes in aSAH, and albumin, where low levels have been associated with poor aSAH outcomes [ 4 , 5 ]. The D-dimer/albumin ratio (DAR) has been identified as an independent predictor of poor outcome in patients suffering from infection, malignancy and critical illness [ 6 , 7 ]. However, the prognostic value of the combination of D-dimer and albumin has not been evaluated in aSAH patients.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of C-reactive protein and albumin levels re ects the prognosis of gastric cancer [30]. Similarly, combined D-dimer level may be useful for predicting patients' response to rst-line chemotherapy and prognosis of advanced gastric cancer [31]. Therefore, we combined cachexia diagnosis with serum biomarker assessment to predict gastric cancer prognosis and patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the immunoblot-based data, HP infection accounted for 89% of the global GC 5 . It was estimated that there were approximately 1.2 million new GC cases worldwide in 2017 6 , indicating that one million cases may be related to HP infection. Surgical resection alone or combined with radiotherapy and chemotherapy is a mainstay of treatment and the only potential cure for GC.…”
Section: Introductionmentioning
confidence: 99%